State Memory Institutions and Modes of Civil Society (Relevant Tomorrow / Aktualu rytoj, 2025)
The literature on civil society acknowledges that civil society plays a very different role at different junctures in the institutional history of any nation. The author of the article discusses the relationship between civil society and state memory institutions using four modalities of civil society: insurgent, institutionalized, anti-democratic, and firewall. Based on examples from the processes characteristic of regime change that have been taking place in Central Europe since 1989, the article attempts to develop a theory that helps to understand this unexplored aspect of memory politics. The study reveals that modes of civil society and the state's relationship with its memory institutions are closely linked to the nature of the current government. The demagoguery that exists today, masquerading as the voice of the people, poses a threat to democracy and provokes the polarization of political views. Such a world puts at risk the professional integrity of the staff of state memory institutions. Political pressure is primarily dangerous to their ability to steward artifacts of the national past according to professional and meritocratic criteria. The politicization of libraries, archives, and universities promotes ignorance rather than knowledge. The safest environment for state memory institutions is a tolerant and pluralistic culture in which they can work without prejudice and be useful to everyone. When illiberal, single-party populist forces rose to power in Hungary and Poland and began to dismantle horizontal accountability mechanisms, their state memory institutions had been under threat of becoming targets in a war of memory, with critics seeking their own political gain.
Keywords: civil society; state memory institutions; regime change; post-communism; backsliding; contentious politics; accountability; Hungary; Poland